Teaching Environmental Sustainability through Technology Education: An Indigenous Perspective - Blose, Princess; Gumbo, Mishack (International Education Trend Issues, 2025)
Environmental sustainability has been a topic of discourse in various fields, including technology. Although the role of technology in environmental sustainability is emphasised, it is underplayed in Technology Education despite having multiple opportunities to promote indigenous knowledge towards environmental sustainability. This descriptive case study explored teaching environmental sustainability through Technology Education at the Mbombela and Mgwenya circuits of the Mpumalanga Province. Content analysis was conducted on Grades 7–9’s Curriculum and Assessment Policy Statement (CAPS), lesson plans, Annual Teaching Plans (ATPs), and Technology Education textbooks. The findings revealed that although CAPS Technology indicates environmental sustainability, it is underplayed in attempts to incorporate indigenous technology in teachers’ lesson plans and ATPs; the textbooks are almost silent on environmental sustainability. The study contributes indigenous perspectives on the opportunity Technology Education offers to teach environmental sustainability. The practical nature of the subject can change learners’ attitudes towards the environment through their learning activities.